SAT0197 Adherence to biologic therapy of rheumatoid arthritis patients – is there any relation with disease activity?. (12th June 2018) - Madeira, N.; Cardoso, A.; Trinca, R.; Silva, C.; Santos, H.; Miguel, C.; Barcelos, F.; Medeiros, D.; Campanilho Marques, R.; Cunha Miranda, L.
Abstract : Background: In the last years, there has been an increase interest in using Patient Reported Outcomes (PROs) in clinical trials and daily clinical practice in Rheumatology to provide patient-centered care. The most frequently reported PROs are patient's pain, patient's global assessment (PGA) of disease activity and reports of functional capacity, fatigue, anxiety and depression. To date, studies that explore patient adherence to rheumatic medications are scarce. Objectives: To study the level of adherence to biologic therapy of Rheumatoid Arthritis (RA) patients, followed at a day care hospital of Rheumatology. Methods: Observational and cross-sectional study which took place in two months of consultation of day care hospital (5 periods per week). Patients with a diagnosis of RA according to 1987 American College of Rheumatology (ACR) and/or 2010 ACR/European League Against Rheumatism criteria, on biologic therapy, able to complete a questionnaire autonomously and who agreed to participate were included. Demographic and clinical data (DAS28, CDAI and SDAI to assess RA disease activity, HADS-A for anxiety, HADS-D for depression, FACIT-F for fatigue) were collected. To assess adherence, a Portuguese version of the Morisky Medication Adherence Scale (MMAS-8) was used and the patients were asked to apply it only to biologic therapy. Three levels of adherence were considered based on the following scores: 0 to <6 (low); 6 to <8 (medium); 8 (high). Statistics: Kruskal-Wallis and Mann-Whitney tests, p<0.05, SPSS® v.23. Results: In total, 61 patients were included, 91.8% female, 82.0% on anti-Tumor Necrosis Factor (anti-TNF), the others on Tocilizumab (16.4%) or Abatacept (1.6%). Table 1 reports the means and medians of demographic and clinical variables included. The mean MMAS-8 score was 7.0±1.2, the median 7.0 (6.8–8.0), with a minimum of 2.5 and a maximum of 8. The adherence was medium in 50.8%, high in 36.1% and low in 13.1% patients. The median of current age was significantly higher for patients with high and medium levels of adherence compared to those with low levels (p=0.030). The time on treatment with the current biologic therapy was significantly different between the levels of adherence (p=0.028); the median of time on treatment for patients with medium levels of adherence was significantly higher comparatively to the other patients (p=0.009). No other significant difference was found among the levels of adherence for the studied variables. Conclusions: The adherence to biologic therapy was at least medium for 86.9% of patients. Differences between levels of adherence were found only for current age and time on treatment. Disease activity of RA does not seem to influence the levels of adherence. Disclosure of Interest: None declared